Mechanical property, biocorrosion and biocompatibility evaluations of a novel Mn-based alloy for future biodegradable vascular stent application - Ang Cai; Zhijie Li; Li Ma; Changshun Wang; Chenglin Li; Mingchang Li (Journal of Materials Research and Technology)
Biodegradable metallic alloys – Mg-based, Zn-based, and Fe-based – have gained prominence as biomaterials for vascular stents. While Mg alloys suffer from rapid corrosion and hydrogen gas generation, Zn alloys demonstrate limited strain hardening capacity. Fe alloys, conversely, display slower degradation rates but present ferromagnetic characteristics that may restrict certain clinical applications. This study explores the potential of Mn-based (Mn–Fe–Cu) alloys as biomedical implants through in vitro and in vivo experiments, comparing them to the standard Mg alloy WE43 as a benchmark. The Mn-based alloy demonstrated exceptional mechanical properties, including an elastic modulus of 130 ± 20 GPa, an ultimate tensile strength of 529 ± 1 MPa, a yield strength of 211 ± 7 MPa, and an elongation of 50.0 ± 0.1 %. Its corrosion rate ranged from 0.02 to 0.14 mm/year, comparable to that of Zn-based alloys. Cytocompatibility assays revealed similar cell viability between the Mn-based alloy and the WE43 magnesium alloy after exposure. The hemolysis ratio was measured at 2.9 %, well below the ISO standard (ISO 1536–2:2004) threshold of 5 %. Additionally, minimal platelet adhesion and activation were observed on the Mn-based materials. In vivo animal studies, conducted via subcutaneous implantation, indicated minimal acute toxicity and immune response to the Mn-based biomaterials. Overall, the Mn-based alloy provides new insights into the development of biodegradable materials and represents a promising candidate for biodegradable vascular stents.